Empirical Assessment of Demographic Factors Influencing Organizational Commitment in Secondary Schools in Kenya - Kimosop, Maurice K. (Machakos University, 2018)
Organizational Commitment (OC) is increasingly becoming an important research concept in the fields of organizational behavior and human resource management. It’s particularly relevant to schools where attainment of organizational goals is highly dependent on teachers’ efforts. The purpose of this paper was to explore the factors that motivate teachers’ commitment to their institutions. The study specifically aimed at establishing whether there is a relationship between teacher’s demographic characteristics (age, gender, academic qualifications, tenure and position held) and School Commitment (SC). The study hypothesized that there is no significant relationship between teachers’ personal characteristics and SC. The study adopted the descriptive research design. The study was conducted in Nakuru County and targeted 1670 secondary school teachers in in four sub-counties. A sample of 310 educators that was selected through stratified random sampling participated in the research. The groups that formed the sample strata comprised of school principals, deputies, heads of department, class teachers and subject teachers. Data was collected using the Allen and Meyer (1990) Three Component Model Employee Commitment Questionnaire. Relationship between variables was established by use of Spearman’s rho and Linear Regression while the level of teacher commitment was established by use of descriptive statistics including means, frequencies and percentages. A high level of SC among Kenyan secondary school teachers was established. Age and the position held in the school was found to be positively related to SC. Negative correlation was established between SC, andacademic qualifications and tenure. There was no significant relationship between gender, and OC. Although a relationship was noted between most demographic variables and SC, the correlations were predominantly low leading to the conclusion that demographics was not a major factor in predicting SC. Consequently, the study recommends that further research be done to explore the other antecedents of SC such as conditions of service and school environment in order to explore their link to teacher commitment.
Keywords: Demographic